Enhancement of biological nitrogen removal performance from low C/N municipal wastewater using novel carriers based on the nano-Fe3O4. (November 2022) - Zhang, Fengyuan; Feng, Quan; Chen, Ying; Shi, Xiaoshuang; Qin, Kang; Lu, Mingyi; Qin, Fan; Fu, Shanfei; Guo, Rongbo
Graphical abstract: Highlights: Magnetic microparticle (MMP) promoted nitrification and denitrification. Addition of MMP buffered the pH variations in the aerobic conditions. MMP promoted the enrichment of bacteria related to nitrogen removal. MMP promoted the production of extracellular polymeric substances. Abstract: The aim of this work was to study the effects of the magnetic microparticles (MMP) on nitrogen removal under low C/N conditions . A 30-day anaerobic/oxic progress illustrated that nitrification and denitrification were promoted in the presence of MMP. MMP could facilitate the production of extracellular polymeric substances (EPS) and act as pH buffering in aerobic conditions. The high-throughput sequencing displayed that, compared with the sludge without MMP, the relative abundance of Dokdonella and Comamonas which are capable of both nitrifying and denitrifying were 8.7% and 1.29% higher in anaerobic sludge and 7.11% and 0.97% higher in aerobic sludge with MMP, respectively. The relative abundance of Pseudomonas with the excellent capability of EPS secretion was also observed 4.33 times higher than that without MMP in the aerobic sludge. Based on the superior performance above, MMP is a promising additive to enhance nitrogen removal efficiency for low C/N wastewater.